Determination of antigenic domain in GST fused major surface protein (Nc-p43) of Neospora caninum - Son, Eui-Sun (The Korean Society for Parasitology, 2001)
The antigenic domain of the major surface protein (Nc-p43) of Neospora caninum was examined by polymerase chain reaction of its gene fragments and recombinant expression as GST fusion proteins. The fragments of Nc-p43 were as follow: a total open reading frame (OFR), T; OFR without signal sequence and C-terminal hydrophobic sequence, S; N-terminal 2/3 parts of S, A; C-terminal 2/3 parts, P; N-terminal 1/3 part, X; middle 1/3 part, Y; and C-terminal 1/3 part, Z, respectively. The DNA fragments were cloned into pGEX-4T vector. Recombinant plasmids transformed into Escherichia coli of BL21 pLysS (DE3) strain were induced to express GST or GST fused fragments of Nc-p43 such as 69 kDa protein for T, 66 kDa for S, 52 kDa for A, 53 kDa for P, and 40 kDa proteins for X, Y, and Z, respectively in SDS-PAGE. The Nc-p43 fragments of T, S, and P reacted with a bovine serum of neosporosis while those of A, X, Y, and Z together with GST did not in the western blot. These findings suggest that the antigenic domain of Nc-p43 of N. caninum may be localized in the C-terminal 2/3 parts. Together with A19 clone in SAG1 of Toxoplasma gondii (Nam et al., 1996), the P fragment of Nc-p43 could be used as efficient antigens to diagnose and differentiate those infections with both species.